An Organic Laser Dye having a Small Singlet‐Triplet Energy Gap Makes the Selection of a Host Material Easier. (2nd June 2020) - Karunathilaka, Buddhika S. B.; Balijapalli, Umamahesh; Senevirathne, Chathuranganie A. M.; Esaki, Yu; Goushi, Kenichi; Matsushima, Toshinori; Sandanayaka, Atula S. D.; Adachi, Chihaya
Abstract: Quenching of singlets by long‐lived triplets is a serious issue for lasing from organic laser dyes, especially under long pulse excitation. As a strategy to scavenge or manage unnecessary triplets, an organic laser dye is dispersed into a host material having high singlet and low triplet energy levels [a large singlet‐triplet energy gap (Δ E ST )]. However, finding such a host material having a triplet scavenging capability is limited. In this study, an organic laser dye, 2, 6‐dicyano‐1, 1‐diphenyl‐λ 5 σ 4 ‐phosphinine (DCNP), having a small Δ E ST of ≈0.44 eV is synthesized, and thus 4‐4′‐bis[( N ‐carbazole)styryl] biphenyl (BSBCz) can be employed as a triplet scavenging host, i.e., the triplets formed on DCNP are easily transferred to BSBCz. A 1 wt%‐DCNP‐doped BSBCz film is formed on a mixed‐order distributed feedback grating, showing lasing with a low threshold value of ≈0.86 µJ cm −2 and a full‐width‐at‐half‐maximum value of ≈0.5 nm. Because of the suppressed singlet‐triplet annihilation, DCNP‐based laser devices operating under a continuous‐wave regime, with a low threshold of 72 W cm −2 and a long laser half‐lifetime of ≈3 min, are demonstrated. These results indicate a possibility of the wider selection of host materials, easing a material design strategy of fabricating high‐performance laser devices in future. Abstract : 2, 6‐dicyano‐1, 1‐diphenyl‐λ 5 σ 4 ‐phosphinine as a semiconductor dye and 4‐4′‐bis[( N ‐carbazole)styryl]biphenyl (BSBCz) as a host are used as the guest–host matrix to realize organic semiconductor lasers with enhancing stability. Lasing is realized in a device based on the DCNP:BSBCz matrix with low thresholds and high photostability.